SURVEILAN INDIVIDU PENDATANG SEBAGAI UPAYA MENCEGAH TRANSMISI COVID-19 DI KOTA PEKALONGAN TAHUN 2020 - Ristiawati Ristiawati; Yuniarti Yuniarti; Nur Lu’lu Fitriyani (LPPM Universitas Pekalongan, 2020)
Corona Virus Disease 2019 (Covid-19) pandemic case has attacked more than 203 countries around the world. WHO states that Covid-19 can be transmitted from person to person through close contact and droplets. The groups most at risk of contracting this disease are people who have contact with Covid-19 patients, including those who treat Covid-19 patients, and people who are treated in infected areas. The purpose of this study was to describe the factors of newcomers, the trend of newcomers and the trend (trend) of positive confirmation cases of Covid-19 in Pekalongan City for the period April-June 2020. This research is an analytical survey research with analytical descriptive research method to present the profiles of Pekalongan residents who fall into the category comer. Based on the results obtained, the total number of immigrants who entered the Pekalongan City area was 1995 (South Pekalongan District with 312 migrants, East Pekalongan 431 migrants, West Pekalongan as many as 548 migrants and North Pekalongan as many as 704 migrants). The trend of arrivals in Pekalongan City for the period April - June 2020 shows a decline at the end of the incident period. The number or the highest peak occurred in the second week of decline with 161 people and the lowest in the VIII week (first week of June 2020) with 19 people. The trend of arrivals is directly proportional to positive cases of Covid-19, which continue to increase every week. The peak of the increase in positive cases of Covid-19 in Pekalongan City occurred in week II (early April 2020) of 12 cases. An increase in these cases came from people returning from international activities. This increase is also due to decreased public awareness in undergoing health protocols according to the Decree of the Minister of Health of the Republic of Indonesia No. HK. 01. 07 / MENKES / 382 in 2020 with the enactment of the New Normal Era.